Stretching prior to resistance training promotes adaptations on the postsynaptic region in different myofiber types - Jacob, Carolina dos Santos [UNESP] (2022)
The morphology of the neuromuscular junction adapts according to changes in its pattern of use, especially at the postsynaptic region according to the myofibrillar type and physical exercise. This investigation revealed the morphological adaptations of the postsynaptic region after static stretching, resistance training, and their asso-ciation in adult male Wistar rats. We processed the soleus and plantaris muscles for histochemical (muscle fibers) and postsynaptic region imaging techniques. We observed muscle hypertrophy in both groups submitted to resistance training, even though the cross-section area is larger when there is no previous static stretching. The soleus postsynaptic region revealed higher compactness and fragmentation index in the combined exercise. The resistance training promoted higher adaptations in the postsynaptic area of plantaris; moreover, the previ-ous static stretching decreased this area. In conclusion, the neuromuscular system's components responded according to the myofiber type even though it is the same physical exercise. Besides, static stretching (isolated or combined) plays a crucial role in neuromuscular adaptations.